The Influence of Implementing Islamic Business Ethics on Increasing Students’ Shopping Interest at Ar-Ridho Modern Islamic Boarding School, Sentul - Baso Pawakkangi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This research is motivated by the importance of integrating Islamic business ethics in the management of pesantren business units, considering that pesantren function not only as educational institutions but also as centers of economic empowerment that should serve as role models for sharia-compliant muamalah practices. The purpose of this study is to analyze the influence of Islamic business ethics principles Tauhid, Tawazun, Hurriyah al-Iradah, and Mas’uliyah—on students’ purchase intention at the Student Cooperative of Pondok Modern Ar-Ridho Sentul. This study employed a quantitative approach, with data collected through questionnaires distributed to 50 student respondents, selected using purposive sampling from a total population of 553 students. The data were analyzed using validity and reliability tests, classical assumption tests, as well as multiple linear regression analysis with T-test and F-test, assisted by SPSS 25 software. The results indicate that three variables of Islamic business ethics, namely Tauhid, Hurriyah al-Iradah, and Mas’uliyah, have a positive and significant effect on students’ purchase intention, while Tawazun shows no significant effect. Simultaneously, all four variables were found to influence purchase intention with a coefficient of determination (R²) of 0.884 or 88.4%, indicating that the majority of variations in students’ purchase intention can be explained by the application of these Islamic business ethics principles.